Measuring and evaluating strategic communications at the Bank of Canada - Annie Portelance (Bank of Canada, 2021)
A central bank's ability to measure the impact of its communications is nothing less than challenging. This is for several reasons: (i) the general public is a vastly broad audience with varying degrees of knowledge of, interest in and engagement with economics and central banking; (ii) some communications goals - such as building trust-take a significant amount of time; (iii) results from communications efforts are often intangible and difficult to measure; and (iv) many communications outcomes are influenced by broader social factors that are beyond a central bank's control. The Bank of Canada's Communications Department has developed a framework to quantify and qualify the Bank's communications efforts and their results. Using data-based measurement and evaluation, the department can assess the impact of the Bank's communications activities and gauge the department's contribution to the Bank's overall goals. These measurement and evaluation activities have contributed significantly to the Communications Department's work, informing both strategic and tactical decisions. The use of measurement and evaluation brings a fresh perspective and enriches the practice of strategic communications-in a sense, integrating science into an established art. The Bank's framework provides a solid foundation upon which measurement and evaluation approaches can stand securely as they evolve.
Keywords: D; D8; D83; 330; Credibility; Monetary policy communications; Central bank research